Islamic Financial Literacy Amongst Muslim Students in Indonesia: A Multidimensional Approach - Muhammad Raihan Aulia Firdausi; Rahmatina Awaliah Kasri (AL-MUZARA'AH, 2022)
Although Indonesia is the largest Muslim country in the world, the level of Islamic financial literacy in Indonesia is still very low. The Islamic financial literacy index in Indonesia is at 8.93%, much lower than the conventional financial literacy index which reached 37.72% in 2019. Therefore, this study aims to analyze the determinants of Islamic financial literacy in Indonesia amongst university students which is a group prioritized by government policies in improving Islamic financial literacy. To achieve this goal, this study develops a multidimensional Islamic financial literacy instrument that includes aspects of knowledge, attitudes and behavior and measures the multidimensional Islamic financial literacy amongst university students. The study collected primary data from 439 students from University of Indonesia and analyzed them using logistic regression method with Islamic financial literacy scores as the dependent variable and socio-demographic factors as the independent variables. The results of this study found that the majority of students (50.1%) had moderate levels of Islamic financial literacy, while 43.5% and 6.4% had high and low levels of Islamic financial literacy respectively. In addition, this study found a positive influence on the field of study, income, and Islamic bank account ownership on the level of Islamic financial literacy. In particular, students who come from the faculty of economics and business, have higher incomes, and have Islamic bank accounts tend to have higher Islamic financial literacy than other students. Based on these findings, relevant stakeholders in Indonesia are expected to continue improving Islamic financial literacy through various strategies and massive educational programs, especially for the groups which have low and moderate Islamic financial literacy. The results of this study are also expected to enrich the literature on Islamic financial literacy in Muslim countries.